Hashimoto’s encephalopathy in psychiatric inpatients: neuropsychiatric morbidity, diagnostic challenges and treatment - İlhan, Rifat Serav and Can, Kazım Cihan and Şahiner, Şafak Yalçın and Duman, Berker and Çolak, Burçin and Kır, Yağmur and Erdoğan, Seyda and Yilmaz, Rezzak and Yücesan, Canan and Araz, Mine and Çınar, Gule and Ünal, Sena and Doğan, Özlem and Uslu, Emine and Saka, Meram Can (Frontiers in Psychiatry, 2025)
IntroductionHashimoto’s encephalopathy (HE) is a rare neuro-inflammatory disorder that poses a significant diagnostic challenge, particularly when its clinical presentation is dominated by psychiatric symptomatology. This study aimed to delineate the constellation of clinical and paraclinical features that differentiate HE from primary psychiatric disorders among seropositive inpatients, thereby facilitating its early and accurate identification.MethodsIn this retrospective, single-center study, the records of 484 consecutively admitted female psychiatric inpatients were reviewed. The final cohort comprised 40 patients with confirmed thyroid autoantibody seropositivity. Patients presenting with atypical features or suspected autoimmune etiologies were subjected to a comprehensive neurodiagnostic evaluation, including cerebrospinal fluid (CSF) analysis, electroencephalography (EEG), MRI, and 18F-fluorodeoxyglucose positron emission tomography (FDG-PET). The diagnosis of HE was established based on stringent criteria, including the exclusion of alternative etiologies and a definitive therapeutic response to corticosteroids.ResultsOf the 40 seropositive patients, nine (22.5%) met the diagnostic criteria for definitive HE. The HE cohort exhibited a significantly later age of psychiatric symptom onset (42.9 vs. 30.1 years; p=0.011) and markedly greater functional impairment (GAF score: 31.7 vs. 51.6; p<0.001) compared to the non-HE group. The most discriminating clinical features were delirium (88.9% in HE vs. 6.5% in non-HE; p<0.001) and catatonia (77.8% vs. 32.3%; p=0.015). Corroborating neurodiagnostic evidence for HE included inflammatory CSF abnormalities (55.6% vs. 0%), diffuse EEG slowing (33.3% vs. 0%), and cortical hypometabolism on FDG-PET (85.7% vs. 0%). All patients with HE were refractory to standard psychiatric interventions but achieved prompt and substantial clinical remission following high-dose corticosteroid administration.DiscussionIn conclusion, HE manifests as a distinct and severe neuropsychiatric syndrome in a subset of seropositive psychiatric inpatients. The emergence of a late-onset clinical picture characterized by a delirium-catatonia complex, particularly when refractory to conventional psychiatric treatment, warrants a high index of suspicion for HE. A multimodal diagnostic approach is essential for accurate identification, enabling the timely initiation of immunotherapy to ameliorate severe neuropsychiatric morbidity and prevent long-term disability